Anti-tuberculosis drug resistance in Slovakia, 2018–2019: The first whole-genome epidemiological study. (February 2022) - Dohál, Matúš; Dvořáková, Věra; Šperková, Miluše; Porvazník, Igor; Cabibbe, Andrea Maurizio; Trovato, Alberto; Spitaleri, Andrea; Rasmussen, Erik Michael; Pršo, Kristián; Škereňová, Mária; Cirillo, Daniela Maria; Solovič, Ivan; et al.
Highlights: The Euro-American lineage 4.7 was the most represented among the XDR-TB/MDR-TB resistant strains. Seven of 12 isolates (58%) belonged to the same recent transmission chain. Strains originally from Eastern European countries were diagnosed in patients without any epidemiological links with these countries. Incidence of resistant XDR-TB/MDR-TB in Slovakia, while low, still should be taken to monitor. Abstract: Objective: The resistance of Mycobacterium ( M. ) tuberculosis to antituberculosis drugs poses a major threat to global public health. Whole genome sequencing (WGS) is an increasingly preferred method in the diagnostics and monitoring of the transmission dynamics of resistant forms of tuberculosis (TB). The aim of the study was to, for the first time, use the sequencing-based analysis to study the transmission and resistance patterns of a systematic and recent collection of extensively drug resistant (XDR) and multidrug resistant tuberculosis (MDR-TB) isolates and to expand our knowledge about drug resistant (DR) TB epidemiological dynamics in Slovakia. Design: A total of 495 patients with pulmonary TB, who were referred to National Reference Laboratory for Mycobacteriology (Vyšné Hágy, Slovakia) in the years 2018–2019, were studied. Out of the total of 495 patients, 4 XDR-TB (0.8%) and 8 (1.6%) MDR-TB isolates were identified by conventional drug susceptibility testing on Löwenstein-Jensen solid medium and subjected to whole genome sequencing. Sequencing data were evaluated for molecular-epidemiological analysis and identification of resistance patterns. Results: Phylogenetic and cluster analysis showed extensive recent transmission events and the predominance of Euro-American lineage 4.7 in Slovakia. However, phylogenetic analysis revealed the circulation of several lineages that originally occurred in Eastern European countries. Resistance patterns for first- and second-line antituberculosis drugs characterized by whole genome sequencing were in high concordance with the results of phenotypic drug susceptibility testing. Conclusion: Forty percent of at least MDR-TB isolates were not genetically linked, indicating that appropriate measures should be taken to monitor and prevent the spread of drug-resistant tuberculosis within the country as well as in other regions.